Synthesis by Thermal Oxidation and Gas Sensing Properties of Fe2O3 Nanorods - Nguyen, Thanh Nghi; Vu, Xuan Hien; Dang, Duc Vuong; Nguyen, Duc Chien (JST: Engineering And Technology For Sustainable Development, 2021)
Iron oxide nanorods were synthesized by thermal oxidation of iron foil in the air at 300-500 oC. The scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to investigate the crystal structures and morphologies properties of the Fe2O3 nanorods. The gas sensing properties of the Fe2O3 nanorods were investigated using a static-gas measuring system in a range of 300-500 oC with the target gases of C2H5OH, CH3COCH3, LPG, and NH3. The results show that Fe2O3 nanorods possess high sensitivity and selectivity toward CH3COCH3. The highest response of 19 was recorded with 1000 ppm CH3COCH3 at the operating temperature of 400 oC.